A taxonomic survey of epiphytes on enhalus acoriodes in Ali Cove, Taklong Asland, Nueva Valencia, Guimaras - Alojado, Ezra Nelson
Epiphytes were collected from the blades of the seagrass Enhalus acoroides which were harvested from Ali Cove, Taklong Island, Guimaras. 20 epiphytic algae were identified with the aid of taxonomic keys. Of these, five belong to the Cyanophyceae, two to the Chlorophyceae, one to the Phaeophyceae, eight to the Rhodophyceae and four to the Bacillariophyceae. Thirteen specimens were identified to the species level only. Measurements of temperature, salinity and pH were taken at the study site during the collection.